ANALISIS INDEKS KESEHATAN MANGROVE DI DESA KERSIK DAN DESA KAMPUNG BARU - Wa wina Sawina (Universitas Teuku Umar, 2022)
The function of the mangrove forest ecosystem to run optimally in the coastal area is very dependent on the health condition of the mangrove itself. This study aims to determine the percentage of canopy cover, the percentage of mangrove forest health conditions and to determine the distribution of individual mangrove species in Kersik Village and Kampung Baru Village. This research activity was carried out in October 2021 using the random sampling method to measure mangrove data parameters. All mangrove data parameters obtained at the location were inputted and analyzed using the MonMang application to determine the mangrove health index (MHI), the percentage of canopy cover, and the distribution of individual mangrove species. The results of the analysis show that the highest percentage of mangrove health index is in Kampung Baru Village, Station I is 57.35%, Station II is 55.20%, and Station III is 56.78%, including in the fairly healthy/good category with low threat. The results of the analysis of canopy cover showed that the highest canopy cover was found in Kampung Baru Village, Station I was 84.85%, Station II was 83.66%, Station III was 85.45% including good category with solid closure. The highest distribution of individual mangrove species is found in Kampung Baru Village, which has 9 distributions of mangrove species Rhizophora apiculata, Rhizophora mucronata, Soneratia alba, Ceriops tagal, Lumnitzera littorea, Lumnitzera racemosa, Avicennia alba, Avicennia marina, Aegiceras floridum.